Investigating the efficacy of virtual reality exposure for crowd management: a real-world application - Alshaer, Abdulaziz (Frontiers in Virtual Reality, 2024)
Crowded spaces, especially during significant events or rituals, pose challenges in terms of safety and management. This study introduces a novel approach to address these challenges by leveraging Virtual Reality Exposure (VRE) as a potential solution. Using the Tawaf ritual around the Kaaba and the specific act of touching the Black Stone as a case study, this research explores how VRE can be employed to alter individual behaviors and perceptions in crowded spaces. Participants completed questionnaires assessing their behaviors and perceptions before and after exposure to visual-only Virtual Reality (VR) and multi-sensory Virtual Reality (MVR) environments.Results indicated a marked decrease in participants' eagerness to physically interact with the Black Stone after the VR exposure. However, this eagerness saw a minor resurgence in the MVR setting, suggesting a more profound sense of immersion. Additionally, the MVR environment significantly enhanced the participants' overall sense of presence and emotional intensity compared to the visual-only VR. This research underscores the potential of VRE as a broader tool for crowd management in various settings, emphasizing its generalizability and contribution to the field. By harnessing the immersive capabilities of VRE, stakeholders can mitigate risks and enhance the experience in crowded scenarios.